Fruit and Veg vs. the Future game - Hess, Tim M.; Craven, Joanne (Cranfield University, 2019)
Fruit and Veg. vs. the Future is a hybrid board / role-play game about water risks in the UK fresh fruit and vegetable system, aimed at industry stakeholders. The game allows players to put together fruit and vegetable systems and pit them against different future scenarios, to see who the winners and losers are and how we can increase the resilience of the overall supply chain to water related risks.These files contain all the playing boards and materials.
Keywords: fruit crop'; 'vegetable crops'; 'drought risk'; 'water scarcity impacts'; 'Horticultural Production not elsewhere classified'; 'Sustainable Agricultural Development'